PERANAN LOGAM SEBAGAI MATERIAL PADA DESAIN PRODUK DAN DESAIN INTERIOR - Arijanto Salmoen Wargadinata (Universitas Trisakti, 2006)
AbstractAs you Imow metallic material's is using for construction that 's way we are talking about metallic. We discript ametalic classified a ferro metalhs as ferro cast iron, steel cast iron also alloy steel and non ferro metallic as alluminium, coper, mgenfums, sincum, plumflum and other alloy of the other up there. Process production of it s are variatie many of processes likes conected methode can disenpfsd .jbr examples I hope the descrffz